Spin reorientation and metamagnetic transitions in R F e0.5 C r0.5 O3 perovskites (R=Tb, Dy, Ho, Er) - Bolletta, Juan Pablo (2018)
In this work we present the magnetic structures and spin reorientation (SR) transitions of the mixed orthochromite-orthoferrite perovskites RFe0.5Cr0.5O3 (R=Tb, Dy, Ho, Er). Magnetization as a function of temperature and external magnetic field as well as neutron powder diffraction measurements were used to characterize the magnetic transitions, including the SR transitions in the transition metal sublattice and the ordering of the rare earth sublattice. The studied compounds order antiferromagnetically below 270 K in a Gx configuration compatible with the Γ4 representation. As temperature decreases, all the compounds show a SR transition from Gx (Γ4) to Gz (Γ2). This transition occurs in a wide temperature range, where both magnetic configurations coexist. Below this SR, the behavior in each case depends on the rare earth. HoFe0.5Cr0.5O3 shows Ho3+ sublattice ordering at a relatively high temperature (45 K). DyFe0.5Cr0.5O3 and ErFe0.5Cr0.5O3 show a second SR transition of the transition metal sublattice, from Gz (Γ2) to Gy (Γ1) at low temperatures (15 and 8 K, respectively). Below these temperatures a metamagnetic (MM) transition is observed for these two compounds at an external magnetic field of H ≈ 7 kOe. The fact that this is only observed for compounds showing Gz (Γ2) to Gy (Γ1) transition suggests that there is a correlation between the Gy (Γ1) order and the MM transition. Finally, TbFe0.5Cr0.5O3 is a peculiar case, since it is the only compound in this family that shows a re-entrant SR to Gx (Γ4) at very low temperatures. By combining these results with previous reports on RFeO3, RCrO3, and RFe0.5Cr0.5O3, we develop a method to qualitatively estimate the SR temperature and the type of transition. We also propose a complete magnetic phase diagram containing the SR transitions and R3+ ordering temperatures for all the RFe0.5Cr0.5O3 (R=Tb, Dy, Ho, Er, Tm, Yb, and Lu) compounds.